Production of the Invasive Aspergillosis Biomarker Bis(methylthio)gliotoxin Within the Genus Aspergillus: In Vitro and in Vivo Metabolite Quantification and Genomic Analysis - Vidal-García, Matxalen; Redrado, Sergio; Domingo, M. Pilar; Marquina, Patricia; Colmenarejo, Cristina; Meis, Jacques F.; Rezusta, Antonio; Pardo, Julian; Galvez, Eva M. (Frontiers in Microbiology, 2018)
Gliotoxin (GT) is a fungal secondary metabolite that has attracted great interest due to its high biological activity since it was discovered by the 1930s. An inactive derivative of this molecule, bis(methylthio)gliotoxin (bmGT), has been proposed as an invasive aspergillosis (IA) biomarker. Nevertheless, studies regarding bmGT production among common opportunistic fungi, including the Aspergillus genus, are scarce and sometimes discordant. As previously reported, bmGT is produced from GT by a methyl-transferase, named as GtmA, as a negative feedback regulatory system of GT production. In order to analyze the potential of bmGT detection to enable identification of infections caused by different members of the Aspergillus genus we have assessed bmGT production within the genus Aspergillus, including A, fumigatus, A. niger, A. nidulans and A. flavus, and its correlation with gtmA presence. In order to validate the relevance of our in vitro findings, we compared bmGT during in vitro culture with the presence of bmGT in sera of patients from whom the Aspergillus spp were isolated. Our results indicate that most A. fumigatus isolates produce GT and bmGT both in vitro and in vivo. In contrast, A. niger and A. nidulans were not able to produce GT or bmGT, although A. niger produced bmGT from a exogenous GT source. The frequency and amount of bmGT production in A. terreus and A. flavus isolates in vitro was lower than in A. fumigatus. Our results suggest that this defect could be related to the in vitro culture conditions, since isolates that did not produce bmGT in vitro were able to synthetize it in vivo. In summary, our study indicates that bmGT could be very useful to specifically detect the presence of A. fumigatus, the most prevalent agent causing IA. Concerning A. terreus and A. flavus a higher number of analyses from sera from infected patients will be required to reach a useful conclusion.